(untitled) (Medical Forum Monthly, 2024)
Objective: To study the presentation and outcome of head injury in paediatric patients managed in Children Hospital & The institute of Child Health, Multan. Study Design: Retrospective Descriptive Study. Place & Duration of Study: This study was conducted in the Deptt. of Paed. Surgery, CH&ICH, Multan, during a period of five years from Jan 2006 to Dec 2010. Patients and Methods: A total of 1150 paediatric patients with head injury were managed in this unit. Data was collected on the basis of history, clinical examination, base line investigations, radiological findings including CT scan, diagnosis and management. Patients were divided into three groups according to the severity of injury based upon Glasgow Coma Scale (GCS). Final analysis and comparison with literature was done. Results: Seventy percent patients were male and 30% female. The age ranged from 1 week to 12 years. Commonest cause was history of fall from height found in 68% cases, followed by road traffic accident 25% and other causes 7%. 70 patients had associated injuries, 5 patients were already mentally handicapped. In 75% cases mild head injury with GCS 14 -15 was present. 35 patients required neurosurgical intervention. 15 patients required treatment for post traumatic seizures. 3 developed brain abscess. 15 patients died in the emergency ward without any surgical intervention within 2 days of admission and 2 died post operatively. Conclusion: Head injury remained a serious problem in paediatric age group with significant morbidity & mortality. Recognizing the pattern of head trauma in children help us to identify high risk groups and environment, which will then help us to design appropriate preventive measures.